Physiographic Analysis as a Conceptual Approach for the Integrated Study of the Landscape. A Case Study of the Usumacinta River watershed, Mexico - Aristides, Saavedra G.; Lopez, L. Daniel M. (European Journal of Applied Sciences, 2022)
In order to conserve and make adequate use of the services provided by the natural system, it is necessary to know it as a whole, as well as each of its components. Physiographic analysis and classification is a conceptual and methodological approach that facilitates the study of the components of the natural environment in an integral manner. The objective of this study is to show the results of the application of this methodology, which consists of a multicategorical and hierarchical system that includes five categories, which in this case only the first three are represented, up to the level of large landscapes. In the discussion of the results, a brief analysis is presented in which the results of the methodology used are compared with the existing cartography of the area. One of the fundamental conclusions is that the physiographic analysis and classification provides and adjusts fundamental elements to the soil mapping and its correlation with the landscape units in geological, geomorphological and climatic terms.